The use of spiral heat exchangers in the ORC domestic systems - Piotr Kolasiński; Zbigniew Rogala (Advances in Mechanical and Materials Engineering, 2015)
One of the problems encountered while designing the ORC systems is the proper selection of the heat exchangers which depends on many factors. Frequently the shell-tube and plate heat exchangers are mainly used in ORC systems. They can be characterized by low ratio of heat flow to heat transfer surface. It influences the size of the heat exchangers, and furthermore, the amount of the material used and the whole installation expense. Interesting alternative for the currently applied heat exchangers might be Rosenblad’s Spiral Heat Exchangers (SHE). What makes this construction so particular is the relatively high ratio of the heat flow to the heat transfer surface. The new design approach dedicated to the Rosenblad’s SHE is presented in this article. The formulated method was applied to the calculations of the Rosenblad’s SHE, which serves as evaporator in the prototype ORC system. The results of the analysis show that the Rosenblad’s SHE is an interesting alternative to other types of the heat exchangers applied presently to the ORC systems. Their application creates a possibility of the reduction of size of the installation, as well as, its expenses.